Avaliação de compósitos á base de celulose bacteriana-hidroxiapatita com peptídeo osteogênico para reparação óssea - Pigossi, Suzane Cristina [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Bacterial cellulose (BC) is a biopolymer in the form nanostructured hydrogel, which is an excellent matrix for the incorporation of others compounds, and at last years, BC has demonstrated promising results for tissue repair. In addition, composites based on BC and hydroxyapatite (BC-HA) is osteoconductor; and when this BC-HA composite associated with the osteogenic growth peptide (OGP) or its C-terminal sequence the pentapeptide OGP (10-14) could be provide osteoinductive properties. This study aimed to evaluate the potential of BC-HA composites with or without OGP and OGP (10-14) in bone repair in critical-size calvarial defect in mice. The analyzed experimental groups were BC-HA, BC-HA-OGP, BC-HA-OGP (10-14) and control group in the respective periods: 3, 7, 15, 30, 60 and 90 days of postoperative. After 3 days of postoperative, bone biomarkers were upregulated mainly by BC-HA OGP and BC-HA OGP (10-14) membranes. In addition, a higher new bone formation was observed in the histomorphometric analysis for BC-HA and BC-HA OGP (10-14) membranes 7 days of postoperative. Similarly, in 60 and 90 days, high percentage of bone formation could be observed in micro-computed tomography analysis for BC-HA and BC-HA OGP (10-14) membranes. High expression of some bone biomarkers, such as Alpl, Spp1 and Tnfrsf11b were also observed for the same membranes 60 and 90 days of postoperative in mice calvarial. In conclusion, the BC-HA and BC-HA OGP (10-14) membranes promoted a better bone formation in critical-size calvarial defects in mice, mainly the BC-HA OGP (10-14) nanocomposite in the early periods of bone repair.

A celulose bacteriana (CB) é um biopolímero sob a forma de hidrogel nanoestruturado, o qual é uma excelente matriz para incorporação de outros compostos, e nos últimos anos a CB tem demonstrado resultados promissores para reparação tecidual. Além disso, compósitos baseados em CB e hidroxiapatita (CB-HA) são osteocondutores, e quando este compósito associado a peptídeos como OGP (osteogenic growth peptide) e a sua sequência C-terminal o pentapeptídeo OGP(10-14) poderão proporcionar-lhe propriedade osteoindutora. O presente estudo avaliou os compósitos CB-HA associados ou não a estes peptídeos para reparação óssea de defeitos críticos em calvária de camundongos. Os grupos experimentais avaliados foram CB-HA, CB-HA OGP, CB-HA OGP(10-14) e controle, nos respectivos períodos de análise: 3, 7, 15, 30, 60 e 90 dias. Após 3 dias de pós-operatório, as membranas CB-HA OGP e CB-HA OGP(10-14) promoveram maiores níveis de expressão dos principais genes marcadores de formação óssea. Além disso, após 7 dias foi observado na análise histomorfométrica que as membranas CB-HA e CB-HA OGP(10-14) promoveram maior neoformação óssea. Semelhantemente, essas membranas apresentaram maiores porcentagens de neoformação óssea como foi observado na microtomografia computadorizada nos períodos de 60 e 90 dias. Maiores níveis de expressão de alguns biomarcadores ósseos, como Alpl, Spp1 e Tnfrsf11b também foram observados para as mesmas membranas em 60 e 90 dias de pós-operatório. Conclui-se que os materiais CB-HA e CB-HA OGP(10-14) apresentaram melhor potencial na reparação óssea em defeitos críticos em calvária de camundongos, destacando o papel osteoindutor nos períodos iniciais de formação óssea da membrana de CB-HA OGP (10-14).
Keywords: Materiais biomédicos; Celulose; Ossos - Crescimento; Cellulose